Credit Analysis of Emerging Economics Energy Distribution Company of Peru (Global Journal of Management and Business Research, 2013)
The case focuses in evaluation of a Peruvian company called â€œThe Energy Distribution Company of Peru â€“ DEPSAâ€. This company has several lines of financing (credit lines or credit facilities) in order to cover their operations in the short and long term. In the last board meeting, they (the board members) agreed that DEPSA should continue with the current financing politic for their operations, focusing on the next 12 months in the short term. In order to confirm the possibility of continuing with that politic, the finance manager had to coordinate with the main bank, the evaluation through a credit analysis and ask for a renewal of its credit lines first in front of the respective financial institution. In addition, the board asked that the regulatory area explains, on the next session, how the Electricity Sector works in Peru does and who are the main actors and stakeholders of the business.
Keywords: electricity sector; financial strategies; financial statements analysis; ratios; dupont; profitability and risks